Effect of comorbidities on survival in patients >80 years of age at onset of renal replacement therapy: data from the ERA-EDTA Registry. Issue 4 (4th February 2021) - Helve, Jaakko; Kramer, Anneke; Abad Diez, Jose Maria; Aresté-Fosalba, Nuria; Arici, Mustafa; Cases, Aleix; Collart, Frederic; Heaf, James; De Meester, Johan; Nordio, Maurizio; Palsson, Runolfur; Pobes, Alfonso; et al.
Abstract: Background: The number of elderly patients on renal replacement therapy (RRT) is increasing. The survival and quality of life of these patients may be lower if they have multiple comorbidities at the onset of RRT. The aim of this study was to explore whether the effect of comorbidities on survival is similar in elderly RRT patients compared with younger ones. Methods: Included were 9333 patients ≥80 years of age and 48 352 patients 20–79 years of age starting RRT between 2010 and 2015 from 15 national or regional registries submitting data to the European Renal Association–European Dialysis and Transplantation Association Registry. Patients were followed until death or the end of 2016. Survival was assessed by Kaplan–Meier curves and the relative risk of death associated with comorbidities was assessed by Cox regression analysis. Results: Patients ≥80 years of age had a greater comorbidity burden than younger patients. However, relative risks of death associated with all studied comorbidities (diabetes, ischaemic heart disease, chronic heart failure, cerebrovascular disease, peripheral vascular disease and malignancy) were significantly lower in elderly patients compared with younger patients. Also, the increase in absolute mortality rates associated with an increasing number of comorbidities was smaller in elderly patients. Conclusions: Comorbidities are common in elderly patients who enter RRT, but the risk of death associated with comorbidities is less than in younger patients. This should be taken into account when assessing the prognosis of elderly RRT patients.